Associations between polypharmacy and treatment intensity for hypertension and diabetes: a cross-sectional study of nursing home patients in British Columbia, Canada. Issue 8 (11th August 2017) - McCracken, Rita; McCormack, James; McGregor, Margaret J; Wong, Sabrina T; Garrison, Scott
Abstract : Objectives: Describe nursing home polypharmacy prevalence in the context of prescribing for diabetes and hypertension and determine possible associations between lower surrogate markers for treated hypertension and diabetes (overtreatment) and polypharmacy. Design: Cross-sectional study. Setting: 6 nursing homes in British Columbia, Canada. Participants: 214 patients residing in one of the selected facilities during data collection period. Primary and secondary outcome measures: Polypharmacy was defined as ≥9 regular medications. Overtreatment of diabetes was defined as being prescribed at least one hypoglycaemic medication and a glycosylated haemoglobin (HbA1c) ≤7.5%. Overtreatment of hypertension required being prescribed at least one hypertension medication and having a systolic blood pressure ≤128 mm Hg. Polypharmacy prescribing, independent of overtreatment, was calculated by subtracting condition-specific medications from total medications prescribed. Results: Data gathering was completed for 214 patients, 104 (48%) of whom were prescribed ≥9 medications. All patients were very frail. Patients with polypharmacy were more likely to have a diagnosis of hypertension (p=0.04) or congestive heart failure (p=0.003) and less likely to have a diagnosis of dementia (p=0.03). Patients with overtreated hypertension were more likely to also experience polypharmacy (Relative Risk (RR))1.77 (1.07 to 2.96), p=0.027). Patients with overtreated diabetes were prescribed more non-diabetic medications than those with a higher HbA1c (11.0±3.7vs 7.2±3.1, p=0.01). Conclusion: Overtreated diabetes and hypertension appear to be prevalent in nursing home patients, and the presence of polypharmacy is associated with more aggressive treatment of these risk factors. The present study was limited by its small sample size and cross-sectional design. Further study of interventions designed to reduce overtreatment of hypertension and diabetes is needed to fully understand the potential links between polypharmacy and potential of harms of condition-specific overtreatment.